Natural resources management in African agriculture : understanding and improving current practices [ - Aboud, Abdillahi A.; Barrett, Christopher B. [ (Christopher Brendan)]; Place, Frank (Wallingford, Oxon, UK : CABI, 2002)
This book synthesizes existing information on the adoption of natural resource management investments and strategies (such as soil fertility improvements or erosion control) for agriculture in sub-Saharan Africa. It also critically examines current analtical methods and generates research and policy recommendations. Topics covered include: farmers' objectives and learning processes; willingness and capacity to make long-term investments; economic incentives and the importance of the resource base; and the agroecological, institutional and policy contexts. The book has 22 chapters and a subject index.
1. Farmers' objective and learning processes -- 2. Willingness and capacity to make long-term investments -- 3. Economic incentives and the importance of the resource base -- 4. The agroecological, institutional and policy context -- 5. Towards improvd natural resource management in African agriculture
Includes bibliographical references (pages 297-329) and index
Keywords: Agricultural resources -- Africa -- Management